Gazal al-Auṭān wa al-Buldān fῑ Syi’r Māni’ Sa’ῑd al-‘Utaibah - Saleh Ahmad Alhameed; Noor Hasma Mohammed Saad; Bader Ulmonir Mohammad Noor (LISANIA: Journal of Arabic Education and Literature, 2023)
The study examines courtly love themes in the homeland and country of the Emirati poet Manaa Saeed al-Otaiba through his two Diwan, "To Where" and "Songs and Wishes." Additionally, it intends to explore the concepts of courtly love and its origins and how to employ poetic imagery and fitting music to achieve the intended results. The poet's feelings are described in the spinning topics based on the places and countries with which he has dabbled, and it is examined how the rhetorical devices and music accompanying those poems were in line with the poet's psychological state. One of the study's conclusions is that he chose separate poetry to express what he wanted to those countries in a fluid manner replete with terms of courtly love. Hence, the titles of those poems explain the content of their verses, and the poet's courtly love extended beyond his native country to countries in the East and West. As if he intended to inform people of the lyre in his heart in many places, the poet selected the new method to be overwhelming in his lyrical poetry. The researcher believes this work has contributions that make it a new building block in the relevant studies of Emirati literature in general and al-Otaiba poetry in particular. As an outstanding poet, he deserves extensive study and research from critics to understand his poetry's substance and multiple purposes.